International Market Access and Poverty in Argentina - Porto, Guido (2012)
This paper examines the impact of access to international agro-manufacture markets on poverty in Argentina. Estimates from the literature suggest that expanded market access would cause the international price of Argentine exports of agro-manufactures to increase by between 8.7% and 15.9%. I explore two poverty effects caused by these prices changes: on food expenditure and on wages. Using a household budget survey, I estimate the impact of higher food prices on the Argentine poverty line. Using a labor force survey, I estimate the responses of wages to changes in export prices. My main finding is that market access would cause poverty to decline in Argentina. From a national head count of 29.26%, the poverty rate would decline to between 28.28% and 28.80%. This means that between 161,000 and 343,000 Argentines would be moved out of poverty.